2001
DOI: 10.1086/319594
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mycoplasma genitalium and Ureaplasma urealyticum in Acute and Chronic Nongonococcal Urethritis

Abstract: One hundred fourteen heterosexual men with acute nongonococcal urethritis (NGU) and 64 patients without NGU were studied. We determined that Chlamydia trachomatis and Mycoplasma genitalium were strongly associated with acute NGU after controlling, by means of multivariate analysis, for age, race, sexual lifestyle, and coinfection (odds ratio [OR], 13.0, 95% confidence interval [CI], 2.6-64.5; and OR, 17.9, 95% CI, 2.0-160, respectively). Eighty-six men with acute NGU reattended at least once 10-92 days after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
134
1
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 20 publications
4
134
1
11
Order By: Relevance
“…El 15 a 25% de los casos agudos de UNG serían causados por M. genitalium y un porcentaje no bien determinado por Ureaplasma sp [5][6][7][8][9]21 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El 15 a 25% de los casos agudos de UNG serían causados por M. genitalium y un porcentaje no bien determinado por Ureaplasma sp [5][6][7][8][9]21 .…”
Section: Discussionunclassified
“…Entre 20 y 60% de los pacientes con UNG aguda, aún tratados con una terapia antimicrobiana apropiada, desarrollan una uretritis crónica, siendo M. genitalium y Ureaplasma sp los agentes más frecuentemente detectados 21 . Hooton y cols investigaron mediante hibridación con sondas de ADN la presencia de M. genitalium en 203 hombres con diferentes tipos de uretritis, determinando la prevalencia del microorganismo según las preferencias sexuales de los pacientes.…”
Section: Discussionunclassified
“…è responsabile di circa il 50% delle uretriti non specifiche (non gonococciche e post gonococciche) (54,93,110). Decorre nel 30-50% dei casi in modo asintomatico o con sintomi lievi e banali (39).…”
Section: Cancro Della Cervice Uterinaunclassified
“…We reported that the M. genitalium load was significantly higher in men with acute nonchlamydial NGU than in asymptomatic men (17). The various results reported to date suggest that M. genitalium may be associated with the development of acute NGU independent of Chlamydia trachomatis (2, 13).For chronic NGU, it has been suggested that persistence of M. genitalium in the urethra after antimicrobial chemotherapy might be associated with this condition (5,7,10,15). However, quantitative analysis of M. genitalium has been not performed in cases of chronic NGU.…”
mentioning
confidence: 99%
“…For chronic NGU, it has been suggested that persistence of M. genitalium in the urethra after antimicrobial chemotherapy might be associated with this condition (5,7,10,15). However, quantitative analysis of M. genitalium has been not performed in cases of chronic NGU.…”
mentioning
confidence: 99%